Integrating structure‐from‐motion photogrammetry into rock weathering field methodologies. Issue 13 (30th July 2019) - Mol, Lisa; Clarke, Lucy
Abstract: Despite recent rapid advances in the field of structure‐from‐motion (SfM) photogrammetry, the use of high‐resolution data to investigate small‐scale processes is a relatively underdeveloped field. In particular, rock weathering is rarely investigated using this suite of techniques. This research uses a combination of traditional non‐destructive rock weathering measurement techniques (rock surface hardness) and SfM to map deterioration and loss of cohesion of the surface using three‐dimensional data. The results are used to interpret weathering behaviour across two different lithologies present on the site, namely shale and limestone. This new approach is tested on seven sites in Longyearbyen, Svalbard, where active weathering of a rock surface was measured after 13 years of exposure to extreme temperature regimes and snow cover. The surface loss was quantified with SfM and combined with rock surface hardness measurement distributions extrapolated in geographic information system (GIS). The combined results are used here to quantify the difference in response of both lithologies to these extreme temperatures. This research demonstrates the potential for further integration of SfM in rock weathering research and other small‐scale geomorphological investigations, in particular in difficult field conditions where portability of field equipment is paramount. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd. Abstract : Using images obtained with a commercially available bridge camera, structure‐from‐motion techniques were used to calculate surface roughness and volume loss at seven experimental sites These measurements were combined with rock surface hardness measurements to map lithology weathering behaviour. This methodology was successfully applied in the High Arctic, where portability of equipment is paramount.